An open chain carboxyethyltin functionalized sandwich-type tungstophosphate based on a trivacant Dawson subunit: synthesis, characterization and properties. Issue 14 (6th March 2015) - Bai, Jian-Ping; Su, Fang; Zhu, Hao-Tian; Sun, Hang; Zhang, Lan-Cui; Liu, Mei-Ying; You, Wan-Sheng; Zhu, Zai-Ming
Abstract : A new Dawson sandwich-type POM–carboxyethyltin derivative assembled in aqueous solution displayed good performance in catalytic and electrocatalytic reactions. Abstract : A Dawson sandwich-type polyoxometalate {C(NH2 )3 }12 H4 [αββα-{(Sn(C3 H4 O2 ))2 Mn2 (P2 W15 O56 )2 }]·22H2 O (abbreviated asSnR-Mn-P 2 W 15 ), functionalized by open chain carboxyethyltin groups, was first prepared in aqueous solution under conventional reaction conditions, and then structurally characterized by physicochemical and spectroscopic methods. Single crystal X-ray diffraction analysis revealed that two Mn 2+ cations and two [Sn(CH2 CH2 COO)] 2+ groups are located in the internal and external positions in the so-called equatorial region ofSnR-Mn-P 2 W 15, respectively. Intriguingly, two exposed carboxyl groups act as stretching-arm brackets, which provide a favorable structure for potential further functionalization. The electrocatalytic activity ofSnR-Mn-P 2 W 15 towards the reduction of hydrogen peroxide and nitrite was studied. Additionally, its acid catalysis and oxidation catalysis activities in organic synthesis were investigated.